The Mental Health of People Living with HIV in China, 1998-2014: A Systematic Review. - Lu Niu; Dan Luo; Ying Liu; Vincent M B Silenzio; Shuiyuan Xiao (PLoS ONE)
Background Understanding the mental health burdens faced by people living with HIV in China is instrumental in the development of successful targeted programs for psychological support and care. Methods Using multiple Chinese and English literature databases, we conducted a systematic review of observational research (cross-sectional, case-control, or cohort) published between 1998 and 2014 on the mental health of people living with HIV in China. Results We identified a total of 94 eligible articles. A broad range of instruments were used across studies. Depression was the most widely studied problem; the majority of studies reported prevalence greater than 60% across research settings, with indications of a higher prevalence among women than men. Rates of anxiety tended to be greater than 40%. Findings regarding the rates of suicidality, HIV-related neurocognitive disorders, and substance use were less and varied. Only one study investigated posttraumatic stress disorder and reported a prevalence of 46.2%. Conflicting results about health and treatment related factors of mental health were found across studies. Conclusions Despite limitations, this review confirmed that people living with HIV are vulnerable to mental health problems, and there is substantial need for mental health services among this population.